Novel Rabbit Model for Femoral Head Osteonecrosis Characterized by Osteoclast Activity and Number of Empty Lacunae - Masri Sihombing; Fitriya Nur Anisa Dewi; Nurjati Chairani Siregar; Dwikora Novembri Utomo; Jeanne Adiwinata Pawitan; Ismail Hadisoebroto Dilogo; Aria Kekalih ((JOINTS) Journal Orthopaedi and Traumatology Surabaya, 2026)
Background: Osteonecrosis, or avascular necrosis (AVN) of the femoral head, is a progressive and irreversible bone pathological condition with an increasing amount of morbidity each year in Indonesia. Testing therapeutic strategies requires an ethical and reliable protocol for inducing femoral head AVN in animal models. This study evaluates a rabbit protocol's feasibility to support a larger investigation into secretome-based treatments.Methods: In this in vivo study, New Zealand white rabbits were divided into three test groups and one control group (n = 3 per group). Methylprednisolone was injected three times at 24-hour intervals, with lipopolysaccharide administered to the third test group on day four. Following a four-week observation period, effects were evaluated using histology, immunohistochemistry, lipid profiles, and radiology.Results: The results showed that both a dose of 20 mg/kgBW methylprednisolone plus 10 μg/kgBW lipopolysaccharide and 20 mg/kgBW methylprednisolone alone resulted in statistically significant femoral head AVN induction, characterized by an increase number of osteoclasts on caspase-3 staining and empty lacunae on hematoxylin–eosin staining. Conversely, the test group with a lower concentration did not show significant differences.Conclusion: These findings support the recommendation of a credible and promising animal model of femoral head osteonecrosis as a basis for the study of osteocytes, osteoblasts, and osteoclast regeneration, along with secretome therapy, which acts as a potential non-surgical treatment option. The absence of radiological confirmation limits a more established analysis, and further studies on this matter are needed.